2011
DOI: 10.1093/infdis/jir757
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Enteroaggregative Escherichia coli From Children in Mali

Abstract: Background. Enteroaggregative Escherichia coli (EAEC) is a cause of epidemic and sporadic diarrhea, yet its role as an enteric pathogen is not fully understood.Methods. We characterized 121 EAEC strains isolated in 2008 as part of a case-control study of moderate to severe acute diarrhea among children 0–59 months of age in Bamako, Mali. We applied multiplex polymerase chain reaction and comparative genome hybridization to identify potential virulence factors among the EAEC strains, coupled with classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
206
5
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(243 citation statements)
references
References 51 publications
24
206
5
8
Order By: Relevance
“…The frequency of adherence fimbria type I-AAF/I (aggA) was the greatest among EAEC isolates from both cases and controls, followed by AAF/III (agg3A), AAF/II (aafA), and AAF/IV (agg4A). These findings were similar to other studies [28,29] where nearly half of clinical EAEC isolates do not possess known major fimbria subunits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The frequency of adherence fimbria type I-AAF/I (aggA) was the greatest among EAEC isolates from both cases and controls, followed by AAF/III (agg3A), AAF/II (aafA), and AAF/IV (agg4A). These findings were similar to other studies [28,29] where nearly half of clinical EAEC isolates do not possess known major fimbria subunits.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggested that sepA is a valuable identification marker for virulent EAEC [18,29]. This study identified less distribution of sepA in EAEC isolates from Thailand compared to previous studies [28,29]. Therefore, the contribution of sepA to EAEC virulence should not be overlooked.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Therefore, we infer the importance of evaluating the grade according to the thickness of the scum layer formed. Results show that 65 (26 strains) harbored one of the AAF genes, which indicates that the frequency of EAEC strains harboring AAF genes in our study is higher than that found in other countries (22,25). The classification of aggR-positive E. coli as EAEC in this study might have contributed to this high figure.…”
Section: Discussioncontrasting
confidence: 45%
“…All isolated EAEC strains were examined for the presence of pCVD432, astA, and 4 AAF encoding genes (aggA, aafA, agg3A, and agg4A) using the primers described in Table 1 (13,20,21,22). The aggA, aafA, agg3A, and agg4A genes respectively encode AAF I, AAF II, AAF III, and AAF IV.…”
Section: O-antigen Typingmentioning
confidence: 99%